Ultrasound-Assisted Encapsulation of Curcumin: RSM Optimization and Release Kinetics - Prasetyaningrum, Aji; Ashianti, Aulia Dwi; Rokhati, Nur; Djaeni, Moh; Ratnawati, Ratnawati; Utomo, Dani Puji (Trends in Sciences, 2025)
Curcumin is a bioactive compound with strong antioxidant properties, yet its application is limited by low aqueous solubility and instability against chemical and metabolic degradation. To enhance its functional performance, curcumin was encapsulated using alginate-chitosan as wall materials assisted by ultrasonic homogenization. Process optimization was conducted through Response Surface Methodology (RSM) with Central Composite Design (CCD), considering sonication time (X1) and ultrasonic power (X2) as independent variables. The analysis of the optimization process demonstrated that the maximum encapsulation efficiency and swelling ratio were realized after 10 min of sonication at a power of 210 W. Compared to the non-ultrasonicated microcapsule, ultrasound treatment significantly enhanced encapsulation efficiency, reduced particle size, and improved homogeneity of the emulsion. Characterization using FTIR confirmed stronger molecular interactions between alginate, chitosan, and curcumin under ultrasound conditions, while SEM micrographs showed rougher surfaces with cracks that facilitated structural integrity. Particle size analysis (PSA) indicated a narrower and more uniform size distribution in the ultrasound-treated samples. Furthermore, the release kinetics analysis was well-fitted to the Peppas-Sahlin model, suggesting a dominant diffusion-controlled mechanism. These results indicate that ultrasonic treatment plays a role in influencing the encapsulation properties of curcumin, although further research is needed to fully understand its effect on the release profile of bioactive substances. HIGHLIGHTS Ultrasonic time and power have a significant effect on curcumin encapsulation. Optimum condition was achieved at sonication time 10 min and power 210 W. Achieved 86.56% encapsulation efficiency and 1.781 swelling ratio. Release kinetics fit Peppas-Sahlin model with diffusion-dominant release. GRAPHICAL ABSTRACT